Analysis of Halal Certification in Small and Medium Industries in the Development of Halal Tourism in Tourism Areas in North Sumatra - Arif, Muhammad; Harianto, Budi; Kumala, Rahima (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Halal Certificate is an important thing for Small and Medium Industries to have in terms of marketing their products and for the economic welfare of the people. Likewise, for Small and Medium Industries located in Tourism Areas where it can develop Halal Tourism in these tourist areas. However, in reality there are many obstacles faced by Small and Medium Industries in terms of issuing these halal certificates. This study uses the Mix Methode research method where the authors conduct Indept Interviews with experts and business people then provide questionnaires to business people regarding the process of making halal certificates for the businesses they run. The procedures for making halal certification for Small and Medium Industries (SMIs) in the development of Halal Tourism in Tourism Areas in North Sumatra include: understanding halal certification requirements and attending halal assurance system (SJH) training, implementing a halal assurance system (SJH), preparing halal certification documents, registering halal certification (uploading data), conducting preaudit monitoring and payment of certification contracts, conducting audits, conducting post-audit monitoring, obtaining halal certificates. The results of this study indicate that only 50% of SMEs understand about halal certificates and procedures for making them. The obstacles in making halal certificates are not believing in the importance of halal certification for their business, not believing in the importance of halal certification for their business. For SMEs that have succeeded in having a Halal Certificate after a simple Linear Regression Test the results show that Halal certificates have a positive and significant effect on SME income of 77.7%.